Exocrine pancreatic insufficiency related fat malabsorption and its association with autonomic neuropathy in Asian Indians with type 2 diabetes mellitus. Issue 5 (September 2021) - Anoop, Shajith; Dasgupta, Riddhi; Jebasingh, Felix K.; Ramachandran, Roshna; Kurian, Mathews Edatharayil; Rebekah, Grace; Balsubramanian, K.A; Thomas, Nihal
Abstract: Background and aims: We aimed to estimate the prevalence of exocrine pancreatic insufficiency (EPI) related fat malabsorption & to correlate it with measures of autonomic neuropathy in patients with T2DM from India. Methods: Patients with T2DM (cases; n = 118) and normo-glycaemic individuals (controls; n = 82) underwent anthropometry and biochemical evaluation at baseline. The 72-hours fecal fat excretion was estimated by the Van de Kamer's titration method. Autonomic neuropathy was evaluated using an automated analyzer. Results: The prevalence of EPI related fat malabsorption in cases was 45% (n = 53; 72 hours mean fecal fat level = 22.7 ± 5.6 g/day). Dysfunctions in the parasympathetic nervous system (PNS; 86.7%; p < 0.05), sympathetic nervous system (SNS; 92.4%; p < 0.05), and both; PNS + SNS (83.1%; p < 0.05) were significant. Amongst measures of PNS dysfunction, there was a significantly higher percentage of abnormal expiration: inspiration ratio (45.3%) and the 30:15 ratio (84.9%) (p < 0.05) in patients with T2DM and EPI related fat malabsorption. Conclusion: In this cross-sectional cohort of Asian Indian patients with T2DM (n = 118), EPI related fat malabsorption correlates significantly with autonomic dysfunction in patients with T2DM. However, these preliminary data need to confirmed in trials with more robust design. Highlights: EPI related fat malabsorption in patients with T2DM were assayed by the 72 h fecal fat assay. The prevalence of EPI related fat malabsorption in patients with T2DM was 45% Parasympathetic nervous system dysfunctions were highly prevalent (86.7%) in patients with T2DM and fat malabsorption.